2023
DOI: 10.1111/jcpe.13833
|View full text |Cite
|
Sign up to set email alerts
|

Porphyromonas gingivalis exacerbates alcoholic liver disease by altering gut microbiota composition and host immune response in mice

Abstract: AimPorphyromonas gingivalis (P. gingivalis), a major periodontal pathogen, increases the risk of systemic diseases. P. gingivalis infection is closely associated with alcoholic liver disease (ALD), but the underlying mechanism remains unclear. We aimed to investigate the role of P. gingivalis in the pathogenesis of ALD.Materials and MethodsAn ALD mouse model was established using a Lieber‐DeCarli liquid diet, and C57BL/6 mice were treated with P. gingivalis to detect the pathological indicators of ALD.ResultsO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…The KEGG enrichment analysis revealed that these crosstalk genes are involved in ALD, the complement and clotting cascade, NF-κB signaling pathway, and Toll-like receptor signaling pathways. Studies have indicated that P. gingivalis can worsen ALD by changing the composition of intestinal microbiota and the immune response of the host [ 20 ]. Moreover, ALD has an increased risk of MS development [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The KEGG enrichment analysis revealed that these crosstalk genes are involved in ALD, the complement and clotting cascade, NF-κB signaling pathway, and Toll-like receptor signaling pathways. Studies have indicated that P. gingivalis can worsen ALD by changing the composition of intestinal microbiota and the immune response of the host [ 20 ]. Moreover, ALD has an increased risk of MS development [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we learned that intestinal permeability and LPS were significantly increased in alcohol-dependent subjects at the onset of withdrawal, suggesting that the gut-liver axis plays an important role in the pathogenesis of alcohol dependence ( Leclercq et al, 2012 ). Gao et al (2023) showed that oral administration of Porphyromonas gingivalis worsened hepatic inflammation in ALD mice by increasing the protein expression of Toll-like receptor 4 (TLR4) and p65, increasing the mRNA expression of IL-6 and TNF-α and up-regulating the production of Transforming Growth Factor β1 (TGF-β 1) and galactaglutinin-3 (Gal-3). Likewise, in alcoholic cirrhosis the intestinal flora remains altered and translocated toward the liver and ascites ( Oesterreicher et al, 1995 ; Naseri et al, 2021 ).…”
Section: Fatty Liver Disease and Gut-liver Axismentioning
confidence: 99%
“…Regrettably, the mechanism of its role in HCC remains to be further studied. Nevertheless, research has demonstrated a close association between oral microorganisms, specifically P. gingivalis, and the development of hepatitis and alcoholic liver disease (Gao et al, 2023). P. gingivalis is capable of inducing intestinal microbial dysbiosis and impairing the integrity of the intestinal mucosal barrier, thereby facilitating the migration of enterobacteriaceae to the liver (Nakajima et al, 2015).…”
Section: Hepatocellular Cancermentioning
confidence: 99%